Cultures of shiverer mutant cerebellum injected with normal oligodendrocytes make both normal and shiverer myelin. - Billings-Gagliardi, S (1984)
Earlier reports suggested that injecting normal optic nerve into organotypic cerebellar cultures from three of the central nervous system hypomyelinated mutant mice resulted in striking local increases in myelination of mutant axons. It has been questioned whether this myelin was produced by the introduced normal glia because there was no "marker" by which the genotype of an individual myelin sheath could be rigorously determined. The present study shows that the myelin sheaths of the central nervous system hypomyelinated mutant shiverer (shi/shi) can be distinguished in vitro from genetically normal myelin by their immunocytochemical reactions and ultrastructure. When shi/shi cultures are injected with normal optic nerve, they produce two kinds of myelin as distinguished by these techniques: shi/shi myelin throughout and, in addition, ultrastructurally and immunocytochemically normal myelin near the optic nerve. These results suggest that the primary defect of the shi/shi mutation involves the oligodendrocyte and support the earlier conclusion that in all of the glial injection experiments to date the genotype of the oligodendrocyte determines the phenotype of the myelin produced.